2018
DOI: 10.1371/journal.pone.0197235
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease influences osteoclastogenic bone markers in subjects with and without rheumatoid arthritis

Abstract: BackgroundPeriodontal disease (PD) and rheumatoid arthritis (RA) are bone pathologies mediated through immuno-inflammatory mechanisms. The aim of this study was to investigate the serum markers osteopontin (OPN), tumor necrosis factor receptors 1 (TNFR1) and 2 (TNFR2) receptor activator of nuclear factor‐kappa B ligand (RANKL) and RANKL/ osteoprotegerin (OPG) ratio and compare them in PD and RA groups.Materials & methodsRA (with PD = 19 and without PD = 19), PD (n = 38) and 14 healthy subjects underwent bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…It causes disruption or deformation of the peripheral joints, and impairs the activities of daily life . Rheumatoid arthritis has been reported to affect ≈ 0.5% to 1.0% of the world's population and ≈ 1.1% of Korean population . Early rheumatoid arthritis causes accumulation of inflammatory cell infiltration in synovial membranes and changes in systemic immune function as the disease progresses .…”
Section: Introductionmentioning
confidence: 99%
“…It causes disruption or deformation of the peripheral joints, and impairs the activities of daily life . Rheumatoid arthritis has been reported to affect ≈ 0.5% to 1.0% of the world's population and ≈ 1.1% of Korean population . Early rheumatoid arthritis causes accumulation of inflammatory cell infiltration in synovial membranes and changes in systemic immune function as the disease progresses .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the panel has been utilized to characterize the inflammatory response during infectious diseases, including leishmaniasis, tuberculosis, urinary tract, HIV, and COVID-19 [36][37][38][39][40] . The panel has also been used to investigate musculoskeletal inflammation during rheumatoid arthritis and in a porcine model of S. aureus bone infection [41][42][43] . PJI and NIAF proteomic profiling using this proteomic platform may give direct evidence towards potential PJI versus NIAF diagnostic biomarkers, avenues for novel treatment options, and provide additional illumination of the inflammatory response during PJI.…”
mentioning
confidence: 99%
“…However, RANK and OPG gene locus polymorphisms are not associated risk factors ( Yang et al, 2019 ). A recent study has shown that RANKL serum concentrations are highest in RA associated with periodontal disease (PD) and that a denosumab treatment suppresses the progression of RA in a randomized controlled trial ( Panezai et al, 2018 ; Tanaka and Tanaka, 2021 ). Lastly, numerous studies have shown that the RRO pathway is involved in bone metastases ( Ono et al, 2020 ; Okamoto, 2021 ) and that the neutralization of RANKL appears to have a beneficial effect on bone health.…”
Section: Rank/rankl/opg In Bone Homeostasis and Diseasementioning
confidence: 99%